2016
DOI: 10.1080/21645515.2016.1140288
|View full text |Cite
|
Sign up to set email alerts
|

The impact and cost-effectiveness of nonavalent HPV vaccination in the United States: Estimates from a simplified transmission model

Abstract: Introduction: The objective of this study was to assess the incremental costs and benefits of the 9-valent HPV vaccine (9vHPV) compared with the quadrivalent HPV vaccine (4vHPV). Like 4vHPV, 9vHPV protects against HPV types 6, 11, 16, and 18. 9vHPV also protects against 5 additional HPV types 31, 33, 45, 52, and 58. Methods: We adapted a previously published model of the impact and cost-effectiveness of 4vHPV to include the 5 additional HPV types in 9vHPV. The vaccine strategies we examined were (1) 4vHPV for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Brisson et al [33] found that if the premium price of the nonavalent vaccine is below $13 per dose, the nine-valent vaccine would be cost saving with respect to the quadrivalent vaccine in the US setting. Robust cost-saving results were also found by Chesson et al [34]. In Europe, the most recent study from Boiron et al [35] showed that vaccinating 60% of girls and 40% of boys aged 9 in Austria with a nine-valent vaccine would substantially reduce the incidence of cervical cancer and be cost effective compared to the current strategy.…”
Section: Introductionmentioning
confidence: 70%
“…Brisson et al [33] found that if the premium price of the nonavalent vaccine is below $13 per dose, the nine-valent vaccine would be cost saving with respect to the quadrivalent vaccine in the US setting. Robust cost-saving results were also found by Chesson et al [34]. In Europe, the most recent study from Boiron et al [35] showed that vaccinating 60% of girls and 40% of boys aged 9 in Austria with a nine-valent vaccine would substantially reduce the incidence of cervical cancer and be cost effective compared to the current strategy.…”
Section: Introductionmentioning
confidence: 70%
“…These studies showed that, in gender-neutral vaccination scenarios, 9vHPV was likely to be cost-effective and even cost-saving compared with 4vHPV. [25][26][27] A later study confirmed the cost-effectiveness of 9vHPV in the United States. 28 In Europe, recent studies in Austria, 29 Germany 30 , Italy 31 and, more recently, in the UK 24 , have also shown the costeffectiveness of 9vHPV in gender-neutral vaccination scenarios.…”
Section: Discussionmentioning
confidence: 96%
“…Of 26 selected studies 12,21-44 on gender-neutral vaccination (three in LMICs and 23 in HICs), two studies examined 2vHPV vaccine, 20 on 4vHPV, and four on 9vHPV vaccines. Sixteen studies [22][23][24][25]27,[36][37][38][39][40][41][42][43][44][45][46] demonstrated that HPV vaccination for heterosexual men with an existing female program was costeffective (ICER = $19,600-52,800/QALY gained in HICs and $49-5,860/QALY gained in LMICs, Table S1) with respect to their respective cost-effectiveness thresholds (Figure 2a).…”
Section: Cost-effectiveness Of Hpv Vaccination For Heterosexual Menmentioning
confidence: 99%
“…All four studies that assessed 9vHPV 36,38,40,42 vaccine concluded that the vaccine for both girls and boys was costeffective (ICER = $8600-49,800/QALY gained, Table S1) in comparison with 2vHPV or 4vHPV vaccination for both women and/or men. The majority (2/3) of studies with 2vHPV vaccination 24,30 was not cost-effective, while 11/20 studies with 4vHPV vaccination were cost-effective.…”
Section: Cost-effectiveness Of Hpv Vaccination For Heterosexual Menmentioning
confidence: 99%
See 1 more Smart Citation